Synthetic glycopeptides and glycoproteins with applications in biological research - Westerlind, Ulrika (Beilstein Journal of Organic Chemistry, 2012)
Over the past few years, synthetic methods for the preparation of complex glycopeptides have been drastically improved. The need for homogenous glycopeptides and glycoproteins with defined chemical structures to study diverse biological phenomena further enhances the development of methodologies. Selected recent advances in synthesis and applications, in which glycopeptides or glycoproteins serve as tools for biological studies, are reviewed. The importance of specific antibodies directed to the glycan part, as well as the peptide backbone has been realized during the development of synthetic glycopeptide-based anti-tumor vaccines. The fine-tuning of native chemical ligation (NCL), expressed protein ligation (EPL), and chemoenzymatic glycosylation techniques have all together enabled the synthesis of functional glycoproteins. The synthesis of structurally defined, complex glycopeptides or glyco-clusters presented on natural peptide backbones, or mimics thereof, offer further possibilities to study protein-binding events.
Keywords: glycopeptide binding; glycopeptides; glycoprotein synthesis; solid-phase peptide synthesis; synthetic vaccines